Management of neck metastases in head and neck cancer: United Kingdom National Multidisciplinary Guidelines - Paleri, V (J Laryngol Otol, 2016)
This is the official guideline endorsed by the specialty associations involved in the care of head and neck cancer patients in the UK. A rational plan to manage the neck is necessary for all head and neck primaries. With the emergence of new level 1 evidence across several domains of neck metastases, this guideline will identify the evidence-based recommendations for management. RECOMMENDATIONS: • Computed tomographic or magnetic resonance imaging is mandatory for staging neck disease, with choice of modality dependant on imaging modality used for the primary site, local availability and expertise. (R) • Patients with a clinically N0 neck, with more than 15–20 per cent risk of occult nodal metastases, should be offered prophylactic treatment of the neck. (R) • The treatment choice of for the N0 and N+ neck should be guided by the treatment to the primary site. (G) • If observation is planned for the N0 neck, this should be supplemented by regular ultrasonograms to ensure early detection. (R) • All patients with T1 and T2 oral cavity cancer and N0 neck should receive prophylactic neck treatment. (R) • Selective neck dissection (SND) is as effective as modified radical neck dissection for controlling regional disease in N0 necks for all primary sites. (R) • SND alone is adequate treatment for pN1 neck disease without adverse histological features. (R) • Post-operative radiation for adverse histologic features following SND confers control rates comparable with more extensive procedures. (R) • Adjuvant radiation following surgery for patients with adverse histological features improves regional control rates. (R) • Post-operative chemoradiation improves regional control in patients with extracapsular spread and/or microscopically involved surgical margins. (R) • Following chemoradiation therapy, complete responders who do not show evidence of active disease on co-registered positron emission tomography–computed tomography (PET–CT) scans performed at 10–12 weeks, do not need salvage neck dissection. (R) • Salvage surgery should be considered for those with incomplete or equivocal response of nodal disease on PET–CT. (R)